2009
DOI: 10.1080/02640410802626567
|View full text |Cite
|
Sign up to set email alerts
|

Muscle activation during low-intensity muscle contractions with restricted blood flow

Abstract: We examined muscle activation during low-intensity muscle contractions with a moderate restriction of blood flow and complete occlusion of blood flow. Unilateral elbow flexion muscle contractions (20% of 1-RM) were performed in Experiment 1 (30 contractions), Experiment 2 (3 sets x 10 contractions), and Experiment 3 (30 repetitive contractions followed by 3 sets x 15 contractions) with moderate restriction, complete occlusion of blood flow or unrestricted blood flow (control). Electromyography (EMG) was record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
193
6
17

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 200 publications
(235 citation statements)
references
References 28 publications
19
193
6
17
Order By: Relevance
“…Further, the average reported score for intensity and discomfort (including pain) for all participants was 11-14 on a scale of 6-20, using the Borg RPE Scale (Borg, 1982). These scores are significantly lower than those reported in previous KAATSU resistance training studies (Takarada et al, 2002;Yasuda et al, 2009) and in HIT studies, which reported intense muscle fatigue and discomfort (Campos et al, 2002;Hurley et al, 1984 [Borg RPE scores were reported as 18 1]). This contrast makes KAATSU-walk training ideal for elderly or frail individuals.…”
Section: Discussioncontrasting
confidence: 42%
“…Further, the average reported score for intensity and discomfort (including pain) for all participants was 11-14 on a scale of 6-20, using the Borg RPE Scale (Borg, 1982). These scores are significantly lower than those reported in previous KAATSU resistance training studies (Takarada et al, 2002;Yasuda et al, 2009) and in HIT studies, which reported intense muscle fatigue and discomfort (Campos et al, 2002;Hurley et al, 1984 [Borg RPE scores were reported as 18 1]). This contrast makes KAATSU-walk training ideal for elderly or frail individuals.…”
Section: Discussioncontrasting
confidence: 42%
“…Importantly, this accumulation of metabolites may increase muscle cell swelling [25], intramuscular anabolic/anti-catabolic signalling [9,26,27], and muscle fibre recruitment [4,28], which are all thought to be beneficial for muscular adaptation [23]. Furthermore, evidence suggests that the hypoxic environment created during BFR may increase the activation and proliferation of myogenic stem cells, enhancing the hypertrophic response [29].…”
Section: Adaptive Responses and Potential Mechanisms Underpinning Bfrmentioning
confidence: 99%
“…Metabolic stress results from the accumulation of metabolic by-products such as H + and Pi 18) . It has been hypothesized that the development of metabolic stress triggers secondary reactions including the recruitment of additional motor units to compensate for the force loss 19) , elevation of systemic hormones 20) , greater acute muscle cell swelling 21) and production of reactive oxygen species (ROS) 22) . These mechanisms may increase the rate of muscle protein synthesis through activation of anabolic and/or prevention of catabolic signaling pathways, leading to hypertrophy [23][24][25][26] as well as the proliferation of satellite cells 27) .…”
Section: Exercise Load and Muscle Hypertrophy In Resistance Trainingmentioning
confidence: 99%